The economic burden and determinant factors of parents/caregivers of children with cerebral palsy in Malaysia: a mixed methods study - Ismail, Aniza; Abd Razak, Ruhana Sk; Suddin, Leny Suzana; Mahmud, Aidalina; Kamaralzaman, Sazlina; Yusri, Ghazali (Multidisciplinary Digital Publishing Institute, 2022)
The economic burden is a major concern for parents/caregivers of children with cerebral palsy (CP). This study used the sequential explanatory mixed-method approach to explorethe economic burden on parents/caregivers with a CP child in Malaysia and the factors associated with the economic burden. The study period spanned April 2020 and December 2020. A total of 106 questionnaire respondents were selected for the quantitative part, and 15 were interviewed to obtain qualitative input. A retrospective costing analysis was conducted based on the cost data obtained from the questionnaire. The majority of the children were GrossMotor Function Classification System (GMFCS) Level 5 (71%), quadriplegic (63%), and aged >4 years (90%). The estimated annual median total economic burden on the parents/caregivers per child in 2020 was RM52,540.00 (~USD12,515.03), with indirect cost being the greatest cost (RM28,800.00, ~USD6860.16), followed by developmental cost (RM16,200.00, ~USD3858.84), direct healthcare cost (RM4540.00, ~USD1081.43) and direct non-healthcare cost (RM3000.00, ~USD714.60). The annual household income was identified as a significant determinant factor (p=0.019, 95% CI: 0.04, 0.40) of the economic burden. The participants' responses during the in-depth interview in the qualitative part of the study supported the premise that socioeconomic factors play a substantial role in determining the total economic burden. Our findings may aid local policymakers when planning the greater provision of support to the affected families in the future, especially for the parents/caregivers of children with CP, who are facing socioeconomic challenges.